Topographic effects during the September 19, 2017 Mexico city earthquake. Issue 125 (October 2019) - Mayoral, Juan M.; De la Rosa, D.; Tepalcapa, S.
Abstract: Seismic waves can significantly amplify in firm soil with abrupt geometric changes due to topographic effects. Moreover, nonlinearities associated with soil layering and geometrical interactions of the incoming waves can lead to changes in frequency content and duration. This paper presents a case study of the effects of the September 19, 2017 earthquake, in the seismic response of a building-hill system 60 m high located in the western part of Mexico City. The performance of the building-hill system was evaluated for this event accounting for site response, topographic, and soil-structure interaction effects, using three-dimensional finite difference models developed with the program FLAC 3D . From the numerical study, the seismic response of the slope was evaluated, accounting for the seismic building-hill interaction effect in the distribution of factors of safety (i.e. capacity over demand), and ground deformations during the event. The damage predicted by the numerical simulation in the building and the hill slope during the 2017 earthquake was in good agreement with that observed during post-earthquake site reconnaissance. To study the effects of the frequency content, seismic intensity, and duration in the distribution of factor of safety and slope deformation patterns, the building-hill seismic response was further studied for subduction and normal events, considering uniform hazard spectra with return period of 250 years. From the results gathered in here, a clear dependency of the expected damage on the hill slope as a function of the seismogenic zone (i.e. subduction or normal) was observed. Graphical abstract: Image 1 Highlights: Observed damage was successfully estimated by the numerical model. Amplification factors were 1.7 in the horizontal, and about 2.0 in the vertical direction. Damage pattern depends on input frequency content, duration, and intensity. For stiff soils ground motion amplification is larger for normal events.